Development of tax havens due to globalization processes and their impact on Czech Republic - Novotný Josef; Kruml Lukáš (Žilinská univerzita, 2015)
Nowadays, companies are increasingly taking advantage of tax havens, which usually generate considerable cost savings. These funds in other circumstances could be used more efficiently within the given country. The main problem in the Czech Republic is the growing interest among companies in taking advantage of the benefits of tax havens. The popularity of tax havens is significantly facilitated by globalization processes and those which usually have a negative impact on every citizen e.g. loss of jobs. This article aims to highlight the issue of tax havens and to propose solutions to their limitation.
Rozvoj daňových rájů vlivem globalizačního procesu a jejich dopad na Českou republiku
Keywords: globalization; tax haven; society; capital; crisis; globalizace; daňový ráj; společnost; kapitál; krize